STAKEHOLDERS’ EVALUATION OF LEARNING OUTCOMES IN EDUCATIONAL QUALITY ASSURANCE SYSTEM - Alexander I. Chuchalin; Marina S. Tayurskaya; Elena A. Muratova (Высшее образование в России, 2016)
The paper reviews the issues relatedto evaluation by key stakeholders (interested parties including employers, alumni, faculty staff and students) of engineering programslearningoutcomes consistent with the list of valuable competences of modern engineer (CDIO Syllabus). On the exampleof Bachelor Program in Electrical Engineering (Tomsk Polytechnic University) the authors discuss the results of comparative analysis of the intended and the acquired levels of proficiency defined by stakeholders for professional and personal attributes of engineering graduates, as well as for their skills to conceive, design, implement and operate technical products and systems in the enterprise, societal, and environmental context. The authors urge to activeimplementation of stakeholders’ evaluation of learning outcomes based on CDIO Syllabus for continuous improvement of educational programs in quality assurance system and professional and public accreditation.